Sport skill evaluation with wearable sensors and statistical analysis - Ishida, K. (Open Journal of Social Sciences, 2019)
This research discusses sport skill evaluation with wearable sensor and statistical analysis. Skateboarding is selected as the target sport to analyze because it will be an official competition in Tokyo 2020 Olympic Games. Skateboarding is one of the difficult sports because of controlling balance to move forward and to get speed on flat ground. The balance control is a basic trick named Tic-Tac, while the trick is difficult for beginners. To make data set for analyzing Tic-Tac skill, we have provided a basic lesson to research participants. After giving them enough self-training time, we put two inertial sensors on a skateboard and waist of a research participant and got total 41 running data with Tic-Tac. According to the result of statistical analysis on the data, we confirmed that swinging a skateboard left and right is the most important motion to generate moving forward driving forth. This result means that inertial sensors are one of the effective tools to evaluate sport skill for sports science and physical education.